THE EFFECTS OF SEWAGE SLUDGE TREATMENT ON TRITICALE STRAW YIELD AND ITS CHEMICAL CONTENTS IN RAINFED CONDITION - M. Yagmur1; D. Arpalı; F. Gulser (Journal of Animal and Plant Sciences, 2017)
This study was carried out to evaluate the effects of different of sewage sludge doses on some yield traits and straw chemical contents in triticale (Triticosecale wittmack, Cv Mikham-2001).The field study was designed in randomized complete blocks (RCB) with 7 sewage sludge treatments (0, 5, 10, 15, 20, 25, 30 t ha-1) and 1 conventional inorganic fertilizer treatment (N, P) with 3 replicates.According to the results of this study, sewage sludge significantly increased grain filling period (day), plant height (cm), straw yield (t ha-1) and biological yield (t ha-1), except harvest index (%). The highest straw yield was obtained from the highest sewage sludge dose (30 t ha-1). Similarly, sewage sludge significantly increased the mineral (N, P, Mg, Mn and Fe) contents of triticale straw in dose dependent manner. Also, sewage sludge did not increase heavy metal (Al, Cd, Ch, Ni, Pb and Cu) concentrations in triticale straw. It was concluded from the results that application of sewage sludge at the rate of 30 t ha-1 was more beneficial in terms of better growth, higher straw yield and some yield traits of triticale under low input soil compared to control and inorganic fertilizer. At the rate of 30 t ha-1sewage sludge application could be substituted for conventional inorganic fertilizer for optimum triticale growth in marginal lands. Also, for agricultural practices, straw material obtained by the rate of 30 t ha-1 application may be recommended for animal feeding operations without any heavy metal risk.
Keywords: Triticale; heavy metal; straw yield; sewage sludge